Desensitizing Toothpastes for Dentin Hypersensitivity: A Network Meta-analysis. (May 2020) - Martins, C.C.; Firmino, R.T.; Riva, J.J.; Ge, L.; Carrasco-Labra, A.; Brignardello-Petersen, R.; Colunga-Lozano, L.E.; Granville-Garcia, A.F.; Costa, F.O.; Yepes-Nuñez, J.J.; Zhang, Y.; Schünemann, H.J.
The goal of this systematic review and network meta-analysis was to compare the relative effects of toothpaste formulations for dentin hypersensitivity (DH), tested in randomized controlled trials (RCTs). We searched 7 databases to February 2019. Paired reviewers independently screened studies, extracted data, and performed risk of bias assessment. The outcome of interest was painful response measured through tactile, cold, and air stimuli. We conducted a random-effects Bayesian network meta-analysis using standardized mean difference (SMD) and their credible intervals (CIs) as the measure of effect for each pain stimuli. We assessed certainty of evidence using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach. We included 125 RCTs (12, 541 patients). For tactile stimulus, the following active ingredients showed large beneficial effects compared to fluoride with moderate certainty of evidence (SMD; 95% CI): potassium + stannous fluoride (SnF2 ) (3.05; 1.69–4.41), calcium sodium phosphosilicate (CSP) (2.14; 0.75–3.53), SnF2 (2.02; 1.06–2.99), potassium + hydroxyapatite (2.47; 0.3–4.64), strontium (1.43; 0.46–2.41), and potassium (1.23; 0.48–1.98). For cold stimulus, CSP showed large beneficial effects compared to fluoride (3.93; 0.34–7.53) with moderate certainty; for air stimulus, arginine (2.22; 1.45–2.99), potassium + hydroxyapatite (2.44; 0.33–4.55), potassium + SnF2 (2.28; 0.87–3.69), CSP (1.98; 0.99–2.98), and SnF2 (1.9; 1.03–2.77) showed large beneficial effects compared to fluoride with moderate to high certainty. Most toothpaste formulations showed evidence of superiority against placebo or fluorides (amine fluoride, sodium monofluorophosphate, or sodium fluoride). CSP was most beneficial for all 3 stimuli with high to moderate certainty. SnF2 alone and potassium combined with SnF2 or hydroxyapatite were beneficial for tactile and air stimulus with high to moderate certainty. Arginine was beneficial for air stimulus, and strontium and potassium were beneficial for tactile stimulus, with moderate certainty.